Evaluation of air pollution tolerant tree species for Kothagiri Municipal Town, the Nilgiris, Tamil Nadu - S, Paulsamy; P, Senthilkumar (Journal of Research in Biology, 2011)
Air pollution tolerance index (APTI) has been determined by pooling the at-tributes viz., total chlorophyll, ascorbic acid and moisture content of leaves and leaf extract pH for certain locally available tree species in and around Kothagiri Municipal Town, the Nilgiris. Of the 24 species analyzed 6 tree species such as Alnus nepalensis, Callistemon lanceolata, Eucalyptus ficifolia, Ficus elastica, Michelia champaca and Toona ciliate recorded higher APTI values. Hence, it is suggested that these tree spe-cies can be given priority for plantation programme in and around industrial com-plexes, road sides and also new urbanized areas in Kotagiri so as to reduce the effect of air pollution and makes the environment clean.